Hilar mossy cells of the dentate gyrus: a historical perspective - Scharfman, Helen E.; Myers, Catherine E. (Frontiers in Neural Circuits, 2013)
The circuitry of the dentate gyrus of the hippocampus is unique compared to other hippocampal subfields because there are two glutamatergic principal cells instead of one: granule cells, which are the vast majority of the cells in the dentate gyrus, and the so-called ‘mossy cells.’ The distinctive appearance of mossy cells, the extensive divergence of their axons, and their vulnerability to excitotoxicity relative to granule cells has led to a great deal of interest in mossy cells. Nevertheless, there is no consensus about the normal functions of mossy cells and the implications of their vulnerability. There even seems to be some ambiguity about exactly what mossy cells are. Here we review initial studies of mossy cells, characteristics that define them, and suggest a practical definition to allow investigators to distinguish mossy cells from other hilar neurons even if all morphological and physiological information is unavailable due to technical limitations of their experiments. In addition, hypotheses are discussed about the role of mossy cells in the dentate gyrus network, reasons for their vulnerability and their implications for disease.